Characteristics of Tigris River bed material at 67 Km Downstream Kut Barrage - Mohammed Siwan Shamkhi; Zainab Shakir Attab (Wasit Journal of Engineering Sciences)
The study reach has a length of about 70 km of Tigris River at downstream Kut barrage. This starts directly after Kut Barrage up to Shiekh Saad south of Kut city. The aim of this study is to analyze the bed material at the bottom of the Tigris River. Twenty-one samples were collected from seven cross-sections by using Van Veen's Grab Sampler. The median diameter (d50) of these samples ranged between 0.005 mm and 0.1 mm  even as the mean size was 0.032 mm. This indicates that the bed material can be classified as fine grain clay, silt, sand  and loam, and also that the percent of washed fine particles near the barrage regulators are larger than those at the other site downstream This could be due to the large water power of released water discharge from the barrage. The flow regime of the first two kilometers of the study reach was flatbed due to the high flow strength of the released water discharged from the barrage.